Mekanisme Peningkatan Heat Shock Protein-70 pada Kanker Payudara Tikus yang Diradiasi, Pascapemberian Ekstrak Meniran (Phyllanthus niruri) (MECHANISM OF INCREASING OF HSP-70 ON IRRADIATED RAT BREAST CANCER, DUE TO APPLICATION OF EXTRACT OF PHYLLANTHUS NIR - Soeprijanto, Bambang; Assegaf, Juliati Hood (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
The used of radiation as a cancer treatment is also proven giving the side effect of damaging thenormal tissue. The extract of Phyllanthus niruri L plant has already been known have an ability to modulatethe immune system. Heat Shock Protein 70 (HSP70) is a protein which can protect other proteins from anydamages. The transcription factor, such as Nuclear factor kappa-light-chain-enhancer of activated B cells(NfkB),is required for protein synthesis. This research was intended to analyze the mechanism, of the immunecompetent cells in expressing the HSP70,through the increase of Nf-kB, at the rat breast cancer tissueunder radiation, due to the application of the extract of P.niruri L plant. An experimental study wasperformed by using the randomized separate pre-test post test controlled group design. The female whiterat (Rattus norvegicus) strain Sprague Dawleystrain, undergoing breast cancer due to the application ofcarcinogen materials 7,12-dimethylbenz(a)antrasen(DMBA) at 20 mg/kg.b.wt, and then the externalradiation at 6Gy given. The treatment group was given the aqueous extract of P.niruri L plant per oral at250 mg/kg b.wt.By immunohistochemistry and t-test study we observe a significant increases in thenumber of cells expressing Nf-kB (p<0.05) and a significant increases in the number of cells expressingHSP70 (p<0.05) at the treatment group. At the regression test, there found to be a stronger influence of NfkBto HSP70 at the treatment group. It is concluded that the mechanism of cell increase expressing theHSP70 at the rat breast cancer tissue under radiation due to the application of the aqueous extract ofP.niruri L plant per oral, is through the increase of cells expressing the Nf-kB.
Keywords: HSP70,Nf-kB, Phyllanthus niruri L, rat breast cancer, and radiation therapy